Shaping Zn Foam Electrodes for CO2 Reduction by Bubbling Electrodeposition: Potentiostatic Versus Galvanostatic Control - Silvia Iacobelli; Olga Russina; Pier Giorgio Schiavi; Francesca Pagnanelli; Pietro Altimari (Chemical Engineering Transactions)
Catalytic zinc foam electrodes for the electrochemical reduction of carbon dioxide to carbon monoxide were synthesized by bubbling electrodeposition. The analysis was focused on analyzing the effect of the employed substrate and of the electrodeposition regime. To this purpose, electrodepositions under galvanostatic and potentiostatic conditions were separately carried out on carbon paper and copper foil. Under galvanostatic conditions, no significant change in the foam pore size (50 µm) was observed by varying the support. In contrast, electrodeposition under potentiostatic conditions resulted in an increase in the pore size with the carbon paper (150 µm) compared to that attained with the copper foil (70 µm). The experimental analysis indicates that this result could be explained by the reduced evolution of hydrogen bubbles and by the decreased number of nucleation sites achieved under the potentiostatic conditions. The catalytic activity of the fabricated electrodes towards the electrochemical reduction of CO2 was evaluated by chronoamperometric tests in an H-cell. Notably, while the efficiency of zinc deposited on the carbon paper electrodes was greater under potentiostatic conditions, the highest Faradaic Efficiency for carbon monoxide production was achieved under galvanostatic conditions (~ 60 % at -1.7 V relative to Ag/AgCl). This discrepancy may be explained by the increased surface area of the electrodes deposited under galvanostatic conditions.